Analysis of CREB-regulated genes in cellular models of Alzheimer's Disease - Role of HDAC inhibitor (s) - Castanheira, Bárbara Isabel Sousa (2022)
Dissertação de Mestrado em Bioquímica apresentada à Faculdade de Ciências e Tecnologia